(untitled) (Journal of the College of Basic Education, 2022)
research aims The current research aims to identify the effect of a counseling program centered on the solution in reducing internet addiction among middle school students I derived a set of hypotheses in light of this goal Identify internet addiction among middle school students.1- 2-Building a counseling centered around the solution to reduce internet addiction among middle school students From the above objectives, the following zero assumptions were derived: 1-There are no statistically significant differences in the average score of the experimental group in reducing internet addiction among middle school students between the pre and post tests. 2-There are no statistically significant differences in the average score of the control group in reducing internet addiction among middle school students between the pre and post tests. 3-There are no statistically significant differences between the mean scores of the experimental group and the control group on Internet addiction in the post test. 4-There are no statistically significant differences in the mean of the experimental group scores in the pre- and postponed tests after a month has passed since the application of the program. The current research came in light of the following results ... As the research results showed that the counseling program was effective in reducing Internet addiction among middle school students, and in the research results, the researcher came up with a set of recommendations and proposals.